HYPERTROPHIC CARDIOMYOPATHY AS A PART OF INHERITED MALFORMATION SYNDROMES IN INFANTS - M.V. Tural'chuk; G.A. Novik; A.Ya. Gudkova (Вопросы современной педиатрии, 2011)
The data of clinical and instrumental examination of two infantile patients with obstructive hypertrophic cardiomyopathy in association with marked multisystem involvement as a picture of inherited malformation syndromes are given.Key words: infants, hypertrophic cardiomyopathy, LEOPARD syndrome, Noonan syndrome.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 166–169)